Condyloma in the nose: clinical snapshot - Streit, Enrico; Gholam, Patrick (Deutsches Ärzteblatt, 2017)
A 45-year-old man presented with a soft, verrucous tumor in the nose that had developed over the preceding 12 months without causing any symptoms other than the mass itself (Figure). He had further tumors of this type on the penis as well as peri-...